2015
DOI: 10.1158/0008-5472.can-14-0629
|View full text |Cite
|
Sign up to set email alerts
|

SYK Is a Candidate Kinase Target for the Treatment of Advanced Prostate Cancer

Abstract: Improved targeted therapies are needed to combat metastatic prostate cancer. Here, we report the identification of the spleen kinase SYK as a mediator of metastatic dissemination in zebrafish and mouse xenograft models of human prostate cancer. Although SYK has not been implicated previously in this disease, we found that its expression is upregulated in human prostate cancers and associated with malignant progression. RNAi-mediated silencing prevented invasive outgrowth in vitro and bone colonization in vivo,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…For instance, Syk plays a role in breast cancer invasive cell growth (19) and acts as an oncogenic driver in small cell lung cancer (20). In addition, upregulated Syk expression corresponds with metastasis of both prostate cancer (21) and squamous cell carcinomas of the head and neck (22). More intriguingly, studies have shown that Syk regulates mTORC1 activation in acute myeloid leukemia and lymphoma (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Syk plays a role in breast cancer invasive cell growth (19) and acts as an oncogenic driver in small cell lung cancer (20). In addition, upregulated Syk expression corresponds with metastasis of both prostate cancer (21) and squamous cell carcinomas of the head and neck (22). More intriguingly, studies have shown that Syk regulates mTORC1 activation in acute myeloid leukemia and lymphoma (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, high Syk expression (mRNA level, n  = 45; protein level, n  = 38) significantly correlated with worse survival, enhanced cell migration and metastases to the lymph nodes in patients with squamous cell carcinomas of the head and neck (Luangdilok et al 2007). Other pro-survival functions of Syk include anti-apoptosis (Geahlen 2014; Krisenko and Geahlen 2015), cancer cell growth and survival (Prinos et al 2011; Udyavar et al 2013; Fei et al 2013), migration and dissemination (Luangdilok et al 2007; Ghotra et al 2015; Katz et al 2005; Krisenko and Geahlen 2015). Yet, other studies suggest that Syk is absent from many highly aggressive epithelial cell-derived tumours (Krisenko and Geahlen 2015; Coopman and Mueller 2006) and Syk may increase cell–cell interactions and limit EMT (Krisenko and Geahlen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SYK is a non-receptor tyrosine kinase expressed in a variety of tissues, in particular in hematopoietic cells. Its role in cancer progression is controversial; in breast cancer it has a tumor suppressor role, while in head and neck and prostate cancer acted as an oncogene [4042]. The role of LGALS1, a member of the lectin superfamily, is more defined; it is involved in different cellular function, as transduction, protein-protein interactions, cell-cycle progression, apoptosis, sustained proliferative signaling, resistance to cell death signals, evasion of immune surveillance, induction of angiogenesis, and activation of the metastatic potential.…”
Section: Discussionmentioning
confidence: 99%